Peran Orangtua Dalam Menanamkan Nilai Agama Dan Moral Pada Anak Usia Dini - Tadzkirah; Tri Ayu Lestari; Suridha (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Educating children is a very important thing for parents to pay attention to because children's development will be greatly influenced by how parents behave in educating children. As parents, there are many roles that are carried out in their lives. One very important role to pay attention to is instilling good attitudes or morals in children from an early age, but not all parents understand or lack awareness of the importance of instilling moral and religious attitudes in children from an early age. This article discusses the role of parents in instilling moral and religious values ​​in early childhood. This research uses qualitative data types with literature review methods from several journals or articles. The results of the study show that parents are the main educators who play a very important role in determining the attitude or character of the child. So that parents are very emphasized to be a good role model in instilling moral and religious values ​​in early childhood.